HUBUNGAN ANTARA ORGANIZATIONAL SILENCE DAN KOMITMEN PUSTAKAWAN DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI DI SUMATERA BARAT - Amiruddin, Amiruddin; Amrina, Yasirli; Andria, Yass (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
(Objectives) This study explores the relationship between organizational silence and librarians' commitment in Islamic State Higher Education Institutions (PTKIN) in West Sumatra. Organizational silence refers to a condition in which employees withhold opinions or information for various reasons, which can negatively impact organizational effectiveness. This phenomenon is often driven by fear of negative feedback, lack of support, and an organizational culture that does not encourage open communication. (Method) A quantitative approach was used, involving librarians from three PTKIN institutions in West Sumatra as respondents. (Findings) The analysis results indicate a significant negative relationship between organizational silence and librarians' commitment. These findings highlight the importance of creating a work environment that supports open communication and values librarians’ contributions. Recommendations for reducing organizational silence include developing an open communication culture, enhancing trust among organization members, and implementing a fair reward system.